The Influence of Social Contagion Within Education: A Motivational Perspective. Issue 4 (3rd October 2018) - Burgess, Laura G.; Riddell, Patricia M.; Fancourt, Amy; Murayama, Kou
ABSTRACT: This article provides an overview of research on social contagion in the context of education. We highlight the importance of students' social interactions in school, considering contagion between peers and contagion from teachers to students, using a motivation perspective. The framework of contagion is introduced broadly, followed by a focused review on social contagion in school environments, both peer and teacher related. Then we introduce methodology for mapping behavior change to networks that are a direct representation of school cohorts. We argue that these different lines of research can be coherently interpreted from a motivation perspective, suggesting the critical role of motivation in social contagion, in the context of education. We highlight the limited amount of research on positive contagion effects and we call for further investigation into ways in which to increase the contagion of positive, academic behaviors. Finally, the neuroscience behind social contagion, both for the mechanisms and the interactions, is discussed.